EXTREME OBESITY AND TOTAL LAPAROSCOPIC HYSTERECTOMY – CASE REPORT - Dokić, Milan; Sljivančanin, Dragiša; Babić, Sandra; Milošević, Branislav (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Previously, the laparoscopic approach was not considered for obese people, because of the increased risk of operative and postoperative complications. In recent years, however, the approach has changed in favor of minimally invasive procedures that avoid laparotomy, which, in obese people, is the most common cause of complications, in the form of slower and aggravated wound healing, bleeding, and infections at the laparotomy site. In emergency situations, extreme obesity accompanied by multiple comorbidities still remains a real challenge for endoscopic surgery, the surgeon and the entire surgical and anesthesiology team. Case report: We present a case of a 61-year-old, extremely obese patient, who was admitted to hospital as an emergency case, due to prolonged vaginal bleeding and anemia. After preoperative preparation, the patient underwent surgery – laparoscopic total hysterectomy with bilateral salpingo-oophorectomy. Conclusion: Obesity is a major problem in modern society. In addition to directly affecting health, excessive body weight in a patient makes it very difficult to perform surgical procedures. The thickness of the abdominal wall and accompanying health problems are a contraindication for laparoscopic operations. In such cases, performing surgery, especially laparoscopic procedures, requires a trained team of professionals and appropriate equipment. Laparoscopic surgery is more and more present, even in the most difficult cases. In presenting this case, we aimed to demonstrate that it is possible to successfully perform total laparoscopic hysterectomy in extremely obese patients with associated health problems, even in emergency situations.